Fretting corrosion characteristics of NC30Fe alloy in a sodium chloride solution - LI Fang; REN Ping-di; ZHANG Xiao-yu; XIANG Hong-xian; REN Si-cong; CAI Zhen-bing (工程科学学报)
By adding an electrochemical test system on a PLINT fretting wear test machine,the fretting corrosion behavior of an NC30 Fe heat transfer tube in a sodium chloride solution was investigated using cross-contacting configuration under different loading conditions,i. e.,three different normal loads of 20,50 and 80 N with a 100 μm reciprocating amplitude. An electrochemical workstation was used to record the open circuit potential during the fretting corrosion process,and the polarization curves were measured by the potential scanning method. The morphology of wear scars was observed by scanning electron microscopy. The 3D morphology and wear volume loss were determined by optical profilometry. It is found that metal atoms in the worn area are more active and more prone to corrosion because of fretting motion,leading to accelerated corrosion of NC30 Fe alloy. As a result of lubrication action by the corrosion product film,the friction coefficient in the sodium chloride solution is smaller than that in pure water. However,the wear volume loss in the sodium chloride solution is greater than that in pure water due to the interaction of corrosion and wear. Abrasive wear and delamination are considered to be the main wear mechanism in the sodium chloride solution.